2022
DOI: 10.1142/s0218271822500535
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic compact star with a linear pressure–density relationship

Abstract: We present a model of compact astrophysical object under General Theory of Relativity using the anisotropic extension of Tolman IV solution. The anisotropy function, derived from the model, remains well behaved throughout the interior of the star. The model satisfies several necessary conditions for a physically realistic compact star. Physical viability of the model is verified specifically by plugging in the estimated parameter values of the Low Mass X-ray Binary (LMXB) candidate 4U 1608–52. Our stability an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Azmat and Zubair [29] considered Drugapal V solution for charged fluid sphere and extended it for anisotropic spherical distribution under the consideration of gravitational decoupling through Minimum Geometric Deformation. Das et al [30] in their model of anisotropic compact star found out the anisotropy function which is physically possible. They also calculated the tidal love number of the star.…”
Section: Introductionmentioning
confidence: 93%
“…Azmat and Zubair [29] considered Drugapal V solution for charged fluid sphere and extended it for anisotropic spherical distribution under the consideration of gravitational decoupling through Minimum Geometric Deformation. Das et al [30] in their model of anisotropic compact star found out the anisotropy function which is physically possible. They also calculated the tidal love number of the star.…”
Section: Introductionmentioning
confidence: 93%
“…[9][10][11][12][13][14][15] The impact of anisotropies in astrophysical and cosmological models have received widespread attention amongst researchers. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] There exists a huge body of work on the effect of anisotropy on the evolution of temperature profiles during dissipative collapse by Govender and coworkers [34][35][36][37][38] and references therein. It has been shown that the presence of anisotropic pressures leads to higher temperatures at each interior point of the collapsing distribution with this effect being prominent in the central regions of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Bhar and collaborators investigated an anisotropic solution in Tolman spacetime [45] and in 2 + 1 dimensions in Finch-Skea spacetime [46]. Some of the recent work on anisotropic compact stars and cosmological modeling can be found in [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%